STUDENT PERCEPTION ON TEACHER CAPABILITIES AND STUDENT LEARNING INTERESTS ON ENGLISH LEARNING ACHIEVEMENTS - Hendrikus Jehamat (Universitas Indraprasta PGRI, 2018)
This research aims to find and analyze: (1) the effect of students' perceptions on the professional abilities of teachers and interest in learning together on the achievement of learning English Private Vocational School Students in North Jakarta. (2) The effect of students' perceptions on the professional abilities of teachers on English language learning achievement of Private Vocational High School students in North Jakarta. (3) The influence of students' interest in learning on the achievement of English learning of private vocational students in North Jakarta. The research method is survey with data analysis using multiple linear regression. Samples were taken as many as 70 students with simple random techniques. The results of the study are as follows: (1) There is a significant influence of students' perceptions of the teacher's professional abilities and interest in learning together on the learning achievement of English private vocational students in North Jakarta. This is evidenced by the acquisition of Sig 0,000 <0.05 and Fcount = 49.399. (2) There is a significant influence of students' perceptions of the professional abilities of teachers on the achievement of English learning of private vocational students in North Jakarta. This is evidenced by the acquisition of sig.0,000 <0.05 and Tcount = 6,381. (3) There is a significant influence of students' interest in learning towards the achievement of English learning of private vocational students in North Jakarta. This is evidenced by the acquisition of Sig. 0.011 <0.05 and Tcount = 2.605. The results of this research are useful to improve the quality of learning and improve English learning achievement at vocational schools.Key Words: student perception; teacher competencies; learning interest; learning achievement